Extended Robotic Pulmonary Resections - Scheinerman, Joshua A.; Jiang, Jeffrey; Chang, Stephanie H.; Geraci, Travis C.; Cerfolio, Robert J. (Frontiers in Surgery, 2021)
While lung cancer remains the most common cause of cancer-related mortality in the United States, surgery for curative-intent continues to be a mainstay of therapy. The robotic platform for pulmonary resection for non-small cell lung cancer (NSCLC) has been utilized for more than a decade now. With respect to more localized resections, such as wedge resection or lobectomy, considerable data exists demonstrating shorter length of stay, decreased post-operative pain, improved lymph node dissection, and overall lower complication rate. There are a multitude of technical advantages the robotic approach offers, such as improved optics, natural movement of the operators' hands to control the instruments, and precise identification of tissue planes leading to a more ergonomic and safe dissection. Due to the advantages, the scope of robotic resections is expanding. In this review, we will look at the existing data on extended robotic pulmonary resections, specifically post-induction therapy resection, sleeve lobectomy, and pneumonectomy. Additionally, this review will examine the indications for these more complex resections, as well as review the data and outcomes from other institutions experience with performing them. Lastly, we will share the strategy and outlook of our own institution with respect to these three types of extended pulmonary resections. Though some controversy remains regarding the use and safety of robotic surgery in these complex pulmonary resection, we hope to shed some light on the existing evidence, and evaluate the efficacy and safety for patients with NSCLC.